Applying Digital Mind Mapping to Support Student Career Planning: The Coggle Approach at SMK GIKI 1 Surabaya - Windasari, Windasari; Supriyanto, Supriyanto; Roesminingsih, Erny; Trihantoyo, Syunu; Hazin, Mufarrihul (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aimed to enhance students’ ability to develop independent career plans by applying the mind mapping technique through the Coggle application. The program employed a coaching approach utilizing the IGROW model, which consists of five key components: Intention, Goal, Reality, Options, and Will/Way Forward. The participants of this training were students from SMK GIKI 1. To ensure a systematic and practical coaching process, the IGROW model was implemented throughout the sessions. The results showed that the training effectively equipped students with the ability to visualize and plan their careers systematically, including mapping their interests, further education goals, and required skills. Evaluation findings indicated a significant improvement in students’ understanding of career planning, as evidenced by the difference between pre-test and post-test scores. Therefore, this training was proven effective in helping students prepare for their future careers in a more structured and potential-oriented manner.